Wishing day - Myracle, Lauren 1969- (Katherine Tegen Books, an imprint of HarperCollinsPublishers, 2016)
Three sisters in the town of Willow Hill participate in a fabled tradition of making three wishes and find out what they really want only after their wishes come true
Keywords: JUVENILE FICTION / Family / Multigenerational; JUVENILE FICTION / Fantasy & Magic; JUVENILE FICTION / Girls & Women; Wishes; Sisters; Magic; Kinderbuch